Transcription of inflammatory cytokine TNFα is upregulated in retinal angiogenesis under hyperoxia - Feng, Yuxi; Chatterjee, Anupriya; Lin, Jihong; Hammes, Hans-Peter (Cellular physiology and biochemistry, 2016)
Background/Aims: Hypoxia induces angiogenesis while hyperoxia promotes vasoregression in the retina. We investigated herein the effect of prolonged hyperoxia on retinal angiogenesis and the underlying mechanism in an oxygen-induced retinopathy (OIR) model. Methods: Vascular morphology was quantified in whole-mount retina from the mice subjected to the conventional OIR model (c-OIR) or the OIR model with prolonged hyperoxia (p-OIR). Expressions of genes related to angiogenesis were determined by real-time PCR. Results: p-OIR retinas showed few intraretinal neovascular tufts at the border of avascular zones, lacking preretinal neovascularization, whereas c-OIR retinas had numerous preretinal neovascularizations. p-OIR retinas demonstrated outgrowth of capillaries in the deep layers despite persistent hyperoxia and possess a larger avascular zone compared with the c-OIR retinas. The capillaries in the p-OIR retinas were well-formed in contrast to those in the c-OIR retinas. p-OIR retinas expressed significantly higher TNFα (∼4 fold) than c-OIR retinas. The expression of vascular endothelial growth factor, Erythropoietin, Angiopoietin 1 and 2 remained unchanged. Conclusion: Our data demonstrate that TNFα transcription is increased in hyperoxia-promoted retinal angiogenesis, implicating it, in association with low VEGF levels, as a possible proponent in retinal angiogenesis under hyperoxia.